2018
DOI: 10.3390/nu10020258
|View full text |Cite
|
Sign up to set email alerts
|

Intake of 3 Eggs per Day When Compared to a Choline Bitartrate Supplement, Downregulates Cholesterol Synthesis without Changing the LDL/HDL Ratio

Abstract: Cardiovascular disease (CVD) risk is associated with high concentrations of low-density lipoprotein cholesterol (LDL-C). The impact of dietary cholesterol on plasma lipid concentrations still remains a concern. The effects of egg intake in comparison to choline bitartrate supplement was studied in a young, healthy population. Thirty participants were enrolled for a 13-week intervention. After a 2-week run-in period, subjects were randomized to consume either 3 eggs/day or a choline bitartrate supplement (~400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 54 publications
8
49
0
Order By: Relevance
“…EY increased the level of serum HDL‐C, and accelerated the secretion of cholesterol and lowered cholesterol absorption, which is inversely associated with the risk of CVD . Previous study investigated the favorable effect of egg intake compared with choline bitartrate supplement on a young and healthy population and showed that EY significantly increased plasma apoA‐I (8%) and apoE (17%), decreased sterol regulatory element‐binding protein 2 and 3‐hydroxy‐3‐methylglutaryl‐CoA reductase expression, and downregulated cholesterol biosynthesis . Other studies demonstrated that egg diet during moderate carbohydrate restriction improved HDL profiles, including modulating HDL phospholipid species composition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EY increased the level of serum HDL‐C, and accelerated the secretion of cholesterol and lowered cholesterol absorption, which is inversely associated with the risk of CVD . Previous study investigated the favorable effect of egg intake compared with choline bitartrate supplement on a young and healthy population and showed that EY significantly increased plasma apoA‐I (8%) and apoE (17%), decreased sterol regulatory element‐binding protein 2 and 3‐hydroxy‐3‐methylglutaryl‐CoA reductase expression, and downregulated cholesterol biosynthesis . Other studies demonstrated that egg diet during moderate carbohydrate restriction improved HDL profiles, including modulating HDL phospholipid species composition .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have shown that EY consumption had beneficial effects on hyperlipidemia by improving the functions of lipoproteins, reducing triglyceride (TG) and cholesterol, and regulating the involved lipid metabolism pathways . Other studies found that egg consumption (3 egg/day) could significantly increase plasma high‐density lipoprotein cholesterol (HDL‐C), apolipoprotein A‐I (apoA‐I) (8%) and apolipoprotein E (apoE), which promoted the cholesterol reverse transport (RCT) to the liver for bile acid synthesis in a young and healthy population . Another study reported that EY intake during carbohydrate restriction affected cholesterol homeostasis in metabolic syndrome (MetS) by increasing lipid transporter ATP‐binding cassette transporter A1 (ABCA1) and 3‐hydroxy‐3‐methyl‐glutaryl (HMG)‐CoA reductase mRNA expression .…”
Section: Introductionmentioning
confidence: 99%
“…Large epidemiological works have been conducted to investigate the effect of egg intake on blood cholesterol levels and risk of CVD in children [123], young people [16, 20, 47, 124], women [1214, 125, 195, 196], men [1214, 125, 195199], and older adults [1214, 125, 195200]. Some have shown that egg consumption did influence the blood cholesterol level but did not increase the risk of CVD in healthy people.…”
Section: The Relationship Between Egg Intake and Cvd Risksmentioning
confidence: 99%
“…In a crossover study conducted with healthy men and women, consumption of 3 eggs per day for 4 weeks reduced PBMC mRNA expression of HMGCR and SREBP2 compared to daily intake of a choline bitartrate supplement [ 108 ]. These findings suggest the whole egg components—such as cholesterol—impact markers of leukocyte cholesterol homeostasis beyond choline fractions.…”
Section: Effects Of Dietary Cholesterol and Egg Intake On Lipoprotmentioning
confidence: 99%
“…These findings suggest the whole egg components—such as cholesterol—impact markers of leukocyte cholesterol homeostasis beyond choline fractions. As described above, egg-induced reductions in HMGCR, LDLR, and SREBP2 mRNA expression observed in overweight and healthy adults may be due to compensatory mechanisms to suppress endogenous cholesterol synthesis and exogenous cholesterol uptake via LDL, presumably due to increased cellular cholesterol loading [ 104 , 105 , 108 ]. Accordingly, postprandial serum following egg intake in healthy men has been shown to increase free cholesterol content of J774 macrophages ex vivo [ 109 ].…”
Section: Effects Of Dietary Cholesterol and Egg Intake On Lipoprotmentioning
confidence: 99%